Green Manufacturing Practices and Green Innovation and Their Role In Sustainable Business Performance Through Culture Green Organization at Small Industrial Enterprises - Hakim, Lukman Nuzul (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
Green Manufacturing Practices and Green Innovation have become an important focus in efforts to achieve sustainable business performance in various sectors, including small industrial companies. Green organizational culture plays a significant role in encouraging the adoption of sustainable practices and innovations within the corporate environment. This study aims to investigate the relationship between green manufacturing practices, green innovation, green organizational culture, and sustainable business performance in small industrial firms. This study uses a descriptive-analytical approach by collecting data from related literature and analyzing green manufacturing practices and green innovation and their role in sustainable business performance through green organizational culture in small industrial companies. The study found that small industrial companies that implement green manufacturing practices and green innovation with the support of a strong organizational culture tend to achieve better business sustainable performance. The results of this study provide a better understanding of the importance of green manufacturing practices, green innovation, and organizational culture in achieving sustainable business performance in small industrial enterprises.